2020
DOI: 10.1111/pce.13709
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil temperature and water content on belowground hydraulic conductance and leaf gas exchange in mature trees of three boreal species

Abstract: Understanding stomatal regulation is fundamental to predicting the impact of changing environmental conditions on vegetation. However, the influence of soil temperature (ST) and soil water content (SWC) on canopy conductance (gs) through changes in belowground hydraulic conductance (kbg) remains poorly understood, because kbg has seldom been measured in field conditions. Our aim was to (a) examine the dependence of kbg on ST and SWC, (b) examine the dependence of gs on kbg and (c) test a recent stomatal optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 90 publications
(151 reference statements)
2
15
0
Order By: Relevance
“…Our results showed that a time-series of TLS intensity measurements can capture from 62 % to 78 % of the variation in ΨL. Our destructive ΨL measurements were complemented with estimated ΨL values that were based on stem diameter change measurements and existing knowledge on the time lag between the change in ΨL and stem diameter (Lintunen et al, 2020). The time lag of 90 minutes that we used is in line with earlier results (Sevanto et al, 2002).…”
Section: Discussionsupporting
confidence: 55%
“…Our results showed that a time-series of TLS intensity measurements can capture from 62 % to 78 % of the variation in ΨL. Our destructive ΨL measurements were complemented with estimated ΨL values that were based on stem diameter change measurements and existing knowledge on the time lag between the change in ΨL and stem diameter (Lintunen et al, 2020). The time lag of 90 minutes that we used is in line with earlier results (Sevanto et al, 2002).…”
Section: Discussionsupporting
confidence: 55%
“…Otherwise, stomatal inhibition of CO 2 gain seems to be the primary and initial control factor, as also may be reflected by the close relationship between both parameters observed for plants of both cultivars in the present study and reported by others (e.g., [21,50,64]. This, however, is quite obvious because of the direct control of stomatal conductance by soil water content, mediated by roots and the abscisic acid (ABA) concentration in the xylem as impressively shown by Bates and Hall [66] almost 40 years ago [67][68][69][70]. In this context, Gao et al [13] pointed out that ABA mediated stomatal but also plant developmental effects are important in the drought stress response of hemp.…”
Section: Seasonal Variation Of Gas Exchange Parameterssupporting
confidence: 85%
“…A recent field and modelling study shows that cold soil decreases belowground hydraulic conductance (i.e. less root water uptake), and further canopy conductance in mature, boreal trees in spring (Lintunen et al 2020). Cold temperature also decreases sink strength (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding stomatal regulation is fundamental in predicting the impact of changing environmental conditions on photosynthetic productivity. Lintunen et al (2020) showed that canopy conductance and soilto-leaf hydraulic conductance are strongly coupled, and that soil temperature and soil water content influences canopy conductance through changes in belowground hydraulic conductance. In particular, the finding that soil temperature strongly influenced belowground hydraulic conductance in mature, boreal trees may help to better understand tree behavior and photosynthetic productivity in cold environments.…”
Section: High-latitude Photosynthetic Productivitymentioning
confidence: 99%